Sectoral Leadership in International Competitiveness: the Portuguese case - Vaz, Elsa Cristina (2012)
The purpose of this paper is to identify the type of labour and the sectors where labour productivity should be improved to elevate the international competitiveness of Portugal. A static multi-sectoral general equilibrium model, with multinational and single-country versions, is used. This model permits the identification of sectors that are leaders in competitiveness improvement. In some countries, traditional export sectors are expected to assume this role, whereas the suppliers of intermediate goods possess the potential to fulfil this function in other countries. The results of this study show that the choice of sector and type of labour are crucial for improving the international competitiveness of the Portuguese economy. The criterion used to measure competitiveness also has an important role. Whereas multifactor productivity is especially increased when the promotion of labour competencies occurs in import and export sectors, population welfare has a greater impact, with the generalised improvement of unskilled labour competencies.